FIBER REINFORCED CEMENT COMPOSITES-IMPROVEMENT OF MECHANICAL AND DEFORMATION PROPERTIES - D. Lj. Jevtić; D. M. Zakić; A. R. Savić (Journal of Engineering & Processing Management, 2009)
This paper presents the results of authors' laboratory testing of the influence of steel fibers as fiber reinforcement on the change of properties of cement composite mortar and concrete type materials.Mixtures adopted - compositions of mortars had identical amounts of components: cement, sand and silica fume. The second type of mortar contained 60 kg/m3 of fiber reinforcement, as well as the addition of the latest generation of superplasticizer. Physical and mechanical properties of fiber reinforced mortars and etalon mixtures (density, flexural strength, compressive strength) were compared. Tests on concrete type cement composites included: density, mechanical strengths and deformation properties. The results showed improvement in the properties of fiber reinforced composites
Keywords: Kompozit; malter; beton; superplastifikator; čelična vlakna